PREMAXILLARY SETBACK OSTEOTOMY AND ALVEOLAR BONE GRAFT FOR PROTRUDING PREMAXILLA - , Hermanto Eddy ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Background: Patients with bilateral cleft lipand palate whose have been performed labioplasty and palatoplasty sometimes faced the problems of protruding premaxilla. Surgicaltechnique for repositioning protruded premaxilla by setback osteotomy, combine with alveolar bone grafting for the correction alignment and closure defect of alveolar cleft. Case description: An 8 years old girl and 19 years old female have been performed labioplasty and palatoplasty with protuding premaxillary. Repositioning the protuded premaxillarywith setback osteotomy and immobilization with intraosseous wire. Bone graft was placed in the alveolar cleft. Results: Setback osteotomy was performed in these patients with no complication and proper positioning of the premaxilla was achieved in all patients. Conclusion: Setback osteotomy premaxillary is simple procedure with a few minor complication but the outcome was satisfactory.